Magnetic resonance vessel wall imaging in cerebrovascular diseases - Diana , Francesco; Strianese, Valentina; Finelli, Mirko; Grazioli , Fabio; Inglese, Luigi Antonio; Ungaro , Gaetano (Journal of Advanced Health Care, 2022)
Cerebrovascular diseases are abnormalities of the intracranial vascular system, affecting its ability to carry blood to the brain. The pathogenesis of many of these begins in the wall of the vessel and actual imaging techniques are not able to visualize the vascular wall. Moreover, perfusion imaging techniques do not provide adequate information on the differentiation, onset or progression of the disease. Recently, imaging of vessel walls with magnetic resonance imaging (VWI) allowed to visualize sub-millimeter structures of the arterial wall, emerging as a valuable technique for understanding and evaluating cerebrovascular diseases. Localization of the lesion and characteristic aspects with contrast medium provide therefore new information on the inflammatory etiology of cerebrovascular diseases, such as intracranial steno-occlusive disease, identification of atherosclerotic plaques, localization of vessel pathology in areas with minimal or zero waist to luminal imaging and stability of the aneurysm allowing early diagnosis and treatment. In recent years, intracranial vessel wall (VW) magnetic resonance (MR) imaging has been an exponential increase in popularity and clinical applicability. However, increasing evidence shows that also the intracranial atherosclerosis might be a potential cause of ischemic stroke, focusing the toward the imaging of the intracranial vasculature. The following descriptive study has been carried out on some patients of the University Hospital “San Giovanni di Dio e Ruggi d’Aragona”, using a 3-T MR. This study describes the effectiveness of the magnetic resonance vessel wall imaging in cerebrovascular diseases.